PENGEMBANGAN PERANGKAT LUNAK ALAT BANTU PERANCANGAN SIKLON SEPARATOR HEMAT ENERGI - Darmanto, Prihadi Setyo; Primanto, Katon (Mesin, 1997)
This paper presents an optimization technique applying the design of the cyclone separators. The results of this optimization technique were the main geometric ratio of the modiï¬ed cyclone (DOPOL), which presented in non-dimensional form, that satisï¬ed the following criteria: minimum pressure drop or maximum separation efficiency. The design procedure of the cyclone was written as the computer software, where the iterative computation design can be proceed faster. This software used the correlations of the cyclone performance obtained by the previous experimental on a modiï¬ed cyclone. The software not only could be applied for modiï¬ed cyclone design, but it also could be used for the design of the classical cyclone base on the well-known algorithm.